2022
DOI: 10.1039/d2ra01767a
|View full text |Cite
|
Sign up to set email alerts
|

Assembly encapsulation of BSA and CCCH-ZAP in the sodium alginate/atractylodis macrocephalae system

Abstract: ZAP and BSA can be encapsulated in the sodium alginate/atractylodis macrocephalae system using an assembly method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…FT-IR analysis was used to identify the functional groups present within the MPs. As shown in Figure 5 , the spectrum of BSA/ALG MPs ( Figure 5 a) indicated that the peak observed at 3356 cm −1 corresponded to an O–H group [ 51 ], and this O–H stretching peak has also been reported for BSA encapsulated in alginate [ 52 ]. This result suggested that BSA was indeed encapsulated within alginate MPs.…”
Section: Resultsmentioning
confidence: 91%
“…FT-IR analysis was used to identify the functional groups present within the MPs. As shown in Figure 5 , the spectrum of BSA/ALG MPs ( Figure 5 a) indicated that the peak observed at 3356 cm −1 corresponded to an O–H group [ 51 ], and this O–H stretching peak has also been reported for BSA encapsulated in alginate [ 52 ]. This result suggested that BSA was indeed encapsulated within alginate MPs.…”
Section: Resultsmentioning
confidence: 91%